Co-occurrence of ectoparasites on wild rodents in Sipora Island, Mentawai, Indonesia with the zoonotic potential review - MAIRAWITA MAIRAWITA; AHMAD MURSYID; DAHELMI DAHELMI; FITHRIA DINIYATI; DELA LIDIA; NOVIKA PUTRI; MARSHA M. ARIFA; JEFRIAL JEFRIAL; RYAN M. MAULANA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Mairawita, Mursyid A, Dahelmi, Diniyati F, Lidia D, Putri N, Arifa MM, Jefrial, Maulana RM. 2023. Co-occurrence of ectoparasites on wild rodents in Sipora Island, Mentawai, Indonesia with the zoonotic potential review. Biodiversitas 24: 6369-6376. A complex interaction between human existence and synanthropic rodents can facilitate the spillover of zoonotic diseases. This research provides valuable data regarding Rodentia species distribution, ectoparasites, and the potential for zoonotic transmission. In linked habitats, rodents were collected systematically using 70 live traps over 3 days. A total of 54 Rodentia individuals were assessed, belonging to 7 species: Mus musculus, Rattus tanezumi, R. tiomanicus, R. rattus, R. argentiventer, R. norvegicus, and Leopoldamys siporanus. Additionally, 7 species of ectoparasites (mites, ticks, and fleas) were identified, including Laelaps echidninus, Leptotrombidium delicense, Haemaphysalis longicornis, Ornithonyssus bacoti, Culicoides sp., Hoplopleura pasifica, and Polyplax spinulosa. Various ectoparasites infested all the captured rats. Laelaps echidninus showed the highest prevalence and relative abundance in plantation habitats (81.25% and 68.81) and human dwellings (72.73% and 89.73). Spearman correlation analysis revealed a strong positive correlation between prevalence-abundance of species ectoparasite (?. 0.955; p-value <0.01), while positive correlations between habitat types-prevalence (?. 0.439; p-value <0.01) and habitat types-abundance of species ectoparasite (?. 0.426; p-value <0.01). Negative correlations between ectoparasites species-prevalence (?. -0.273; p-value <0.05) and ectoparasites species-abundance of species ectoparasites (?. -0.309; p-value <0.05). These findings emphasize the need to assess zoonotic risks and take effective control measures in island regions for public health and conservation.